2004
DOI: 10.1002/aic.10066
|View full text |Cite
|
Sign up to set email alerts
|

Diesel particulate matter and NOx removals using a pulsed corona surface discharge

Abstract: A pulsed corona surface discharge (PCSD) system was established for particulate matter (PM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…They found that the NTP reactor has effects on the oxidation of PM in diesel exhausts at a low temperature; PM can be removed at an energy efficiency of 2.9 g/kWh. Also in 2000, we reported that carbon (activated carbon) oxidation using a pulsed spark discharge has an energy efficiency as high as 4-10 g/kWh, which implied that PM removal using such a plasma discharge has potential for practical use as an after treatment method for diesel exhausts [12].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the NTP reactor has effects on the oxidation of PM in diesel exhausts at a low temperature; PM can be removed at an energy efficiency of 2.9 g/kWh. Also in 2000, we reported that carbon (activated carbon) oxidation using a pulsed spark discharge has an energy efficiency as high as 4-10 g/kWh, which implied that PM removal using such a plasma discharge has potential for practical use as an after treatment method for diesel exhausts [12].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental apparatus consists of a diesel engine (Toyota, 2 liter, 4-cycle, direct injection) and a hydro dynamometer test cell equipped with a performance measurement system, which was described in detail elsewhere [18,19]. The diesel engine was operated at an output of 3.0 kW and the flow rate of exhaust gas was 76 Nm 3 /h.…”
Section: Methodsmentioning
confidence: 99%
“…Extensive literature has provided information on the mechanism of PM oxidative removal, simulation of PM oxidation, and experiments using real exhaust gases [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Related with the mechanism of PM oxidative removal, the oxidation mechanism of carbon materials (such as graphite and carbon nanotube) are helpful as the main component of PM is graphite-like carbon of graphene basic structural element.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…to form molecular nitrogen (N 2 ), NO 2 , nitrous acid (HNO 2 ) or nitric acid (HNO 3 ). 20,21 Previous studies have also showed that a corona discharge in air may lead to a production of NO x at 3.6 ϫ 10 14 molecules/J of energy input. 25 Ozone (O 3 ) is a byproduct of the nonthermal plasma reactor and its generation rate is governed by the amounts of atomic oxygen (O) principally generated by the reaction of excited nitrogen and oxygen molecules (N 2 * and O 2 *) with the molecular oxygen (O 2 ).…”
Section: Introductionmentioning
confidence: 98%